القانون الجنائي الإسلامي ومدى إمكانية تطبيقه في الدول الإسلامية: العقبات والحلول = Islamic criminal law and the extent in which could be apply in Islamic countries: obstacles and solutions - Laeba, Muhammad (2015)
The main objective of the application of Islamic Criminal Law Islamic and non Islamic Countries is to establish a stable society which enjoys peace and contentment. The equality between its different categories is being applied, and the injustice, corruption as well as the obliqueness is restricted. Especially, the different criminal activities and high jacking of the right of the weak people becomes publically practiced due to the circumstances and the changes facing many Muslim Societies with regard to security, political and economic instability. Therefore, the study will try to clarify the issues concerning Islamic Criminal Law such as its concept, significant as well as its features. In addition, the study will also discuss the obstacles of application of Islamic Criminal Law in both Islamic and non Islamic Countries with presenting some solutions and suggestions for them.